The Analysis Study of Prevalence, Risk Factor, Management of First Trimester Uterine Rupture: A Comprehensive Systematic Review - Nita, Niken Septia; Wardatul W.S, Rizki (International Medical Journal Corp. Ltd, 2024)
Background: Most uterine ruptures occur in pregnant women, though it has been reported in non-pregnant women when the uterus is exposed to trauma, infection, or cancer. The aim: The aim of this study to show about prevalence, risk factor, management of first trimester uterine rupture. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Uterine rupture in the first trimester of pregnancy is a rare and life-threatening occurrence that can be safely and conservatively treated. The main driving factor behind a scarred uterus is previous caesarean section. Delay in definitive management causes significant fetal morbidity and mortality. For best outcomes, vaginal birth after a previous cesarean section needs close monitoring in appropriately prepared units with the ability to perform immediate cesarean delivery and provide advanced neonatal support.